The Sscs Learning Model (Search, Solve, Create, and Share): Its Effectiveness on Students’ Learning Outcomes at Smp Negeri 5 Bandar Lampung - Listia, Kory; Fitriani, Fitriani; Azizah, Nurul; Baharudin, Baharudin; Octafiona, Era (FKIP - Universitas Riau, 2025)
This research is motivated by the importance of improving students’ learning outcomes in the cognitive domain at the C4 level (analysis), which is a crucial component of higher-order thinking processes. The purpose of this study is to examine the effect of problem-based learning models on students’ learning outcomes at the analysis level. This study employs a quantitative approach with a quasi-experimental posttest-only control group design. The research sample consists of two eighth-grade classes at SMP Negeri 5 Bandar Lampung, selected using simple random sampling. Class VIII.6, serving as the experimental group, received instruction through a problem-based learning model, while class VIII.8, serving as the control group, received conventional instruction. The instrument used was a multiple-choice test consisting of five valid items, with a reliability coefficient of 0.673. Data analysis was conducted using prerequisite tests and an independent samples t-test. The results showed a significance value of 0.073 > 0.05, indicating that H₀ is accepted. Therefore, there is no significant difference between the learning outcomes of the experimental group and the control group. In conclusion, the implementation of the problem-based learning model did not have a significant effect on improving students’ analytical skills compared to conventional teaching methods.